Influência da taxa de aplicação superficial em um sistema francês de wetlands construídos no tratamento de esgoto de um restaurante universitário - Leite, Camila de Lourdes Ferreira (2019)
Wetlands constructed are alternative systems for the treatment of effluents, they are attractive due to the potentiality in the decentralization of effluent treatment and the low costs of implantation and operation. In this context, the present study had as objective to verify the influence of the surface application rate on the removal of total nitrogen in a Frances de Wetland Constructed system employed in the effluent treatment of the university restaurant of the Universidade Tecnológica Federal do Paraná. The experimental unit is located in the dependencies of the UTFPR - Campus Londrina and the monitoring took place over the course of 4 weeks. Three batches (0.1m³ / m².d, 0.2m³/ m².d and 0.3m³/m².d) were applied to obtain the flow hydrograms for the laboratory analyzes. Samples were collected at the exit of the system and the samples were submitted to physical chemical analysis, being nitrite, nitrate and ammoniacal nitrogen. Nitrite concentrations were found to be very low or close to zero. The relevant presence of nitrite was not detected in any of the samples, the concentration of nitrate was 0.73 mg/L to 1.21 mg/L, and the values found were not relevant. There was no detection of ammoniacal nitrogen in the different rates of surface applications, this means that the increase of the application rate did not affect the oxidation of the ammonia, practically being totally oxidized in the different rates of application. According to the flow rate found in the hydrographs, the flow peaks increase according to the increase of the surface application rate. The results show that the correlation between the efficiency of the system and the flow hydrograms of the different rates of surface application was not found.